P-484 Oocytes quality assessment in breast cancer: implications for fertility preservation. (30th June 2022) - Fabiani, C; Guarino, A; Meneghini, C; Licata, E; Paciotti, G; Miriello, D; Schiavi, M; Spina, V; Rago, R
Abstract: Study question: Does the breast cancer (BC) influence the oocyte quality and ovarian response to controlled ovarian hyperstimulation (COH) for fertility preservation (FP) in female oncology patients? Summary answer: The diagnosis of breast cancer does not seem to be associated with an impairment of ovarian reserve, but with a worsening of oocyte quality. What is known already: Fertility preservation in female oncology patients should be integrated as part of management of cancer patient to improve their quality of life. Every day in Italy about 30 new cases of cancer are diagnosed in patients with age under 40 years and BC is the most common malignancy in women undergoing fertility preservation. Currently mature oocyte cryopreservation is a standard technique for fertility. The studies on the outcome of ovarian response after ovarian stimulation in specific cancer patients are limited. Only few reports have suggested a deleterious impact of the oncological disease on quality of follicular growth and ovarian function. Study design, size, duration: This is a retrospective single-center case-control study carried out in the IVF ( in vitro fertilization) Unit at the Sandro Pertini Hospital in Rome between 2016 and 2021. The aim of this study is to investigate the effect of BC on number, above all on quality of oocyte and on dysmorphic oocyte ratio, in oncology patients compared to women age- and date-matched controls undergoing COH for IVF for male or tubal factor infertility. Participants/materials, setting, methods: A total of 294 women were enrolled in the study: 105 women affected by breast cancer in the case group and 189 healthy women in the control group. Boths groups were comparable in terms of age, body mass index (BMI) and antimulleran hormone (AMH) value, E2 level at triggering day, total FSH cumulative dose, stage, histotype, BRCA status and hormone receptors. The primary outcome was number and quality of retrievd oocyte from ovarian pick-up (OPU). Main results and the role of chance: There were no significant differences in terms of basal fertility indices between the 2 groups: median AMH levels were 2.3 ng/mL in BC patients and 2.8 ng/mL in control group (p = 0.103). The median length of stimulation was 11 days in both groups. The median of total immature oocytes (oocytes MI + germinal vesicle) was 2 in cancer patients and 0 in control group (p < 0.0001). Finally, the median of total dysmorphic oocytes were 1 in cancer group vs 0 (p < 0.0001). The multivariable analysis identified the cancer as risk factors of presence of dysmorphic oocytes (OR (95%CI):3.92 (1.84-8.35). Moreover either in the case and control group age, BMI, AMH, duration of stimulation, E2 level at triggering day, total FSH cumulative dose and, only for BC patients, stage, histotype, BRCA status and hormone receptors were not statistical significantly associated with the presence of dysmophic oocytes. Finally, our data confirmed that the cancer is the only risk factors not only for the presence of dysmorphic oocytes, but also respect to the number of dysmorphic oocytes and to the percentage of dysmorphic oocytes respect to the total number of retrieved oocytes for patient. Two patients have had a spontaneous pregnancy. Limitations, reasons for caution: The limitations concern the paucity of specific cancer group especially BRCA mutated BC patients and the different triggers for induction of final maturation. We still have not a follow up data to evaluate the competence of vitrified MII oocytes for oncology patients and we cannot report information on spontaneous births. Wider implications of the findings: The BC diagnosis is a four times greater risk factor in retrieving dysmorphic oocytes, but the stage of BC does not influence the number of retrieved dysmorphic oocytes. Further studies are necessary to evaluate the etiopathogenetic mechanisms underlying oocyte abnormalities in specific group of female oncology patients. Trial registration number: 0104898/2020